Optimizing Photosynthesis Active Radiation, PAR: Creating Stable Light Environments for Indoor Farming using reflector. - ZULKEFLI, NUR ADLIN SAKINAH; Akmal Nizam Mohamed (Research Progress in Mechanical and Manufacturing Engineering, 2025)
Agriculture has evolved to become more innovative in parallel with technology advancements, as seen by the rise in demand for food that meets strict quality requirements and has a high nutritional value. One example of this is the development of vertical farming (VF). Without relying on seasonality to affect output, VF is a competitive system for sustainable food production that minimizes the need for land, natural resources, and labor in agriculture. It may be built at any time and wherever in the world. When it comes to VF, light is the most crucial component to take into consideration. Production increases dramatically when artificial light, especially LED lighting, replaces sunlight. A sophisticated kind of precision farming known as "plant factories" involves growing every crop in carefully regulated conditions with exact lighting, humidity, temperature, and nutrient levels. However, the previous study used experiments to assess PAR levels, light intensity distribution, and the ways in which these variables influenced plant growth parameters. The results demonstrate that strategically positioned reflectors significantly increase PAR in the plant canopy, leading to more consistent and higher-quality yields. Through the use of reflectors, this study will optimize photosynthesis active radiation, or PAR and also create stable light environments for indoor farming.